The coming death : traces of mortality across East Asia - Calichman, Richard (State University of New York Press, 2022)
"Explores questions of death and mortality in several key texts of East Asian literature and cinema"-- Provided by publisher.
Keywords: Death in motion pictures.; Mortality in motion pictures.; Death in literature.; Mortality in literature.; Motion pictures -- East Asia -- History.; East Asian literature -- History and criticism.; Mort au cinéma.; Mortalité au cinéma.; Mort dans la littérature.; Mortalité dans la littérature.; Littérature extrême-orientale -- Histoire et critique.; SOCIAL SCIENCE / Ethnic Studies / Asian Studies.; Death in literature; Death in motion pictures; East Asian literature; Mortality in literature; Mortality in motion pictures; Motion pictures; East Asia; Criticism, interpretation, etc.; History